Peripheral inflammation preceeding ischemia impairs neuronal survival through mechanisms involving miR‐127 in aged animals. Issue 1 (28th December 2020) - Loppi, Sanna; Korhonen, Paula; Bouvy‐Liivrand, Maria; Caligola, Simone; Turunen, Tiia A.; Turunen, Mikko P.; Hernandez de Sande, Ana; Kołosowska, Natalia; Scoyni, Flavia; Rosell, Anna; García‐Berrocoso, Teresa; Lemarchant, Sighild; et al.
Abstract: Ischemic stroke, the third leading cause of death in the Western world, affects mainly the elderly and is strongly associated with comorbid conditions such as atherosclerosis or diabetes, which are pathologically characterized by increased inflammation and are known to influence the outcome of stroke. Stroke incidence peaks during influenza seasons, and patients suffering from infections such as pneumonia prior to stroke exhibit a worse stroke outcome. Earlier studies have shown that comorbidities aggravate the outcome of stroke, yet the mediators of this phenomenon remain obscure. Here, we show that acute peripheral inflammation aggravates stroke‐induced neuronal damage and motor deficits specifically in aged mice. This is associated with increased levels of plasma proinflammatory cytokines, rather than with an increase of inflammatory mediators in the affected brain parenchyma. Nascent transcriptomics data with mature microRNA sequencing were used to identify the neuron‐specific miRNome, in order to decipher dysregulated miRNAs in the brains of aged animals with stroke and co‐existing inflammation. We pinpoint a previously uninvestigated miRNA in the brain, miR‐127, that is highly neuronal, to be associated with increased cell death in the aged, LPS‐injected ischemic mice. Target prediction tools indicate that miR‐127 interacts with several basally expressed neuronal genes, and of these we verify miR‐127 binding to Psmd3 . Finally, we report reduced expression of miR‐127 in human stroke brains. Our results underline the impact of peripheral inflammation on the outcome of stroke in aged subjects and pinpoint molecular targets for restoring endogenous neuronal capacity to combat ischemic stroke. Abstract : Peripheral inflammation preceeding ischemic stroke impairs neuronal survival specifically in the elderly. This increased vulnerability is associated with downregulation of the expression of miR‐127, in both animals and humans. Our results reveal novel molecular targets for treating ischemic stroke, and underline the impact of peripheral inflammation on the outcome of stroke in aged subjects.